Potensi Energi Air Sebagai Sumber Energi Listrik di Daerah Wonosobo - Wijayanto, Rizal; ., Yushardi; ., Sudarti (Jurnal Pendidikan, Sains Dan Teknologi, 2023)
Water energy is indispensable in meeting the needs of all creatures, water energy sources that can be obtained for free must be utilized and maintained as well as possible. Especially in areas that have a large enough potential water source, this potential can later be utilized primarily as a source of electrical energy. Electrical energy is very much used in human activities, so in the process of utilization it must be used as much as possible. With the existence of water energy sources, it will greatly help save energy in this era of rapid development. Wonosobo is one of the areas that has a high potential for water energy sources. This is because the area in Wonosobo has quite high rainfall and a tropical climate, with many streams and water sources scattered in each area. That way it can be maximized regarding the use of water energy sources for power plants located in Wonosobo.